IMPLEMENTASI ASESMEN DIAGNOSTIK DALAM MENGIDENTIFIKASI KEBUTUHAN BELAJAR SISWA SEKOLAH DASAR - Diana Susanti; Barokah Isdaryanti; Wiwi Isnaeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of the Merdeka Curriculum has prompted a transformation in the paradigm of educational evaluation, shifting the focus from learning outcomes to learning processes that are centered on students’ needs and characteristics. This study aims to comprehensively examine the implementation of both cognitive and non-cognitive diagnostic assessments in identifying the learning needs of elementary school students during the period from 2021 to 2026. This research employed a Systematic Literature Review (SLR) approach by analyzing relevant scientific publications to map the patterns of diagnostic assessment implementation, identify the challenges faced by teachers, and formulate practical solutions applicable in school settings. The findings indicate that the use of cognitive diagnostic assessments integrated with the Teaching at the Right Level (TaRL) approach, along with non-cognitive assessments focusing on students’ learning characteristics and preferences, effectively supports the optimization of differentiated instruction. However, implementation in practice continues to face several challenges, including limited time allocation, teachers’ insufficient capacity to develop valid and reliable assessment instruments, and inadequate access to continuous professional development opportunities. Based on these findings, this study recommends the development of a digitally integrated assessment ecosystem combined with the strengthening of teacher learning communities as a sustainable strategy to enhance the quality of diagnostic assessment implementation in elementary schools.